Assessing Mitochondrial Movement Within Neurons: Manual Versus Automated Tracking Methods. (12th May 2015) - Bros, Helena; Hauser, Anja; Paul, Friedemann; Niesner, Raluca; Infante‐Duarte, Carmen
<x xml:space="preserve">Abstract</x> Owing to the small size of mitochondria and the complexity of their motility patterns, mitochondrial tracking is technically challenging. Mitochondria are often tracked manually; however, this is time‐consuming and prone to measurement error. Here, we examined the suitability of four commercial and open‐source software alternatives for automated mitochondrial tracking in neurons compared with manual measurements. We show that all the automated tracking tools dramatically underestimated track length, mitochondrial displacement and movement duration, with reductions ranging from 45 to 77% of the values obtained manually. In contrast, mitochondrial velocity was generally overestimated. Only the number of motile mitochondria and their directionality were similar between strategies. Despite these discrepancies, we show that automated tools successfully detected transport alterations after applying an oxidant agent. Thus, automated methods appear to be suitable for assessing relative transport differences between experimental groups, but not for absolute quantification of mitochondrial dynamics. Although useful for objective and time‐efficient measurements of mitochondrial movements, results provided by automated methods should be interpreted with caution. <inline-graphic xlink:href="ark:/27927/pgj1m9qb3dx" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />